2012
DOI: 10.1155/2012/516283
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Equilibrium of Standing on One Leg at Various Life Stages

Abstract: The ability to maintain a one-leg standing position and the relation between plantar two-point discrimination and standing time on one leg were assessed. Participants were 1,241 apparently healthy people aged 2–92 years. Participants were asked to stand on one leg with eyes open (EO group) or closed (EC group) for up to 120 seconds. Coefficients of determination (COD) between subjects' ages and results for both groups were calculated by quadratic and cubic functions. The slope of the tangent line drawn against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
1
13
0
2
Order By: Relevance
“…They considered themselves relatively healthy and appeared to be highly functioning, though many of them had several concurrent medical conditions. The range of their OLST with EO is in line with those in the literature for older adults ( Morioka et al, 2012 ). Therefore, we decided to also include the two subjects with well-regulated diabetes mellitus and the one with neurofibromatosis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…They considered themselves relatively healthy and appeared to be highly functioning, though many of them had several concurrent medical conditions. The range of their OLST with EO is in line with those in the literature for older adults ( Morioka et al, 2012 ). Therefore, we decided to also include the two subjects with well-regulated diabetes mellitus and the one with neurofibromatosis.…”
Section: Discussionsupporting
confidence: 89%
“…This finding was unexpected as aging leads to a decline in mechanical properties of the skin, as well as cutaneous receptor density, morphology, and physiology ( Kenshalo, 1986 ; Peters, McKeown, Carpenter, & Inglis, 2016 ; Shaffer & Harrison, 2007 ). Morioka et al (2012) found a significant correlation between age and somatosensation in subjects between 2 and 92 years old. Thus, the non-significant correlation between age and TSPT or VPT in our cohort might be explained by the rather narrow age span (60-78) and maybe by the subjects being relatively healthy.…”
Section: Discussionmentioning
confidence: 75%
“…Aging is associated with the deterioration of standing balance [ 27 ]. Moreover, maintaining SLS is more challenging for elderly people [ 28 ]. In this study, AREA-SD was larger in the elderly group than in the young group under the FR condition, and this finding is in agreement with previous results [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto a la evaluación de la estabilidad, al utilizar el gesto de apoyo unipodal, en niño/ as menores de 6 años predomina el control de esta postura por medio de la aferencia visual, explicación del porqué a esta edad se logran mejores resultados en la prueba con oa (5). Además, el desarrollo de este componente no es lineal y se ha documentado que se acelera al final de la edad preescolar (22). Al respecto, los resultados de esta investigación indican que en la prueba de apoyo unipodal con oc existe una tendencia de los niños/as rurales a tener mejor estabilidad con oc, esto probablemente se relacione con la mayor variabilidad de movimientos que se ejecutan en terrenos irregulares, por lo que el aprendizaje motor se ve mayormente favorecido en estos niños/as.…”
Section: Discussionunclassified
“…Se permitieron 3 intentos que registraban el mejor resultado en centímetros. El balance fue medido con la prueba de caminar sobre una línea recta según el protocolo de Bürgi et al y usando zapatos; mientras que la estabilidad se midió utilizando el protocolo de apoyo unipodal de Morioka et al (21)(22). Por último, la flexibilidad fue valorada mediante la prueba de alcanzar sentado en V, extraído del The President's Challenge Physical Activity, Nutrition & Fitness Awards Program (23).…”
Section: Materiales Y Métodosunclassified